Regulation of Antibiotic Production by Signaling Molecules in Streptomyces - Kong, Dekun; Wang, Xia; Nie, Ju; Niu, Guoqing (Frontiers in Microbiology, 2019)
The genus Streptomyces is a unique subgroup of actinomycetes bacteria that are well-known as prolific producers of antibiotics and many other bioactive secondary metabolites. Various environmental and physiological signals affect the onset and level of production of each antibiotic. Here we highlight recent findings on the regulation of antibiotics biosynthesis in Streptomyces by signalling molecules, with special focus on autoregulators such as hormone-like signalling molecules and antibiotics themselves. Hormone-like signalling molecules are a group of small diffusible signaling molecules that interact with specific receptor proteins to initiate complex regulatory cascades of antibiotic biosynthesis. Antibiotics and their biosynthetic intermediates can also serve as autoregulators to fine-tune their own biosynthesis or cross-regulators of disparate biosynthetic pathways. Advances in understanding of signalling molecules-mediated regulation of antibiotic production in Streptomyces may aid the discovery of new signalling molecules and their application use in eliciting silent antibiotic biosynthetic pathways in a wide range of actinomycetes.